THE USE OF COSTS IN SETTING SELLING PRICES. - Mason, Perry (The Accounting Review, 1926)
Abstract This article focuses on the use of costs in setting up selling prices. In almost every presentation of the advantages and purposes of a cost accounting system the possibility of using costs as the basis for fixing selling prices is given special attention. In so far as the individual producer can not set his own selling prices he needs a better cost system and more detailed analyses of cost data in order to compete successfully in the market. Price determination is a complex process with many interrelating forces and proceeding largely by trial and error methods. Even the monopolist, setting prices at will in order to get the highest possible return, must know his costs in order to compare the net return from different prices. Cost, then, can sometimes be used as a direct basis from setting selling prices, is often one of the important factors in the determination of provisional selling prices, but many times the problem of the individual producer is to keep his costs below a selling price determined by general market forces and conditions.